Pencak Silat sebagai Warisan Budaya: Identitas Lokal Seni Silat Ulu Ambek di Pariaman, Sumatera Barat - Ilham, Wahyu; Musa, Nurul Muttaqin; Amin, Ruzita Mohd. (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Lhokseumawe, 2023)
Abstract: This study aims to discover a model for preserving the art of Pencak Silat as a cultural heritage and local identity of the Pariaman community. Method: This qualitative research utilizes a descriptive survey. Results: The findings indicate that the cultural control of the Pariaman community indirectly impacts the development of the art of Pencak Silat. For the Pariaman community, Pencak Silat has inclusion criteria, checks balance, cognitive function, musculoskeletal status, fitness, metabolic effects, and psychological health. Furthermore, the sociopsychic and characteristics of the community's Silat assist in modifying behavior in troubled adults and teenagers. The Pariaman community has a Pencak Silat art named